If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -1) = x + 3 Reorder the terms: 7(-1 + x) = x + 3 (-1 * 7 + x * 7) = x + 3 (-7 + 7x) = x + 3 Reorder the terms: -7 + 7x = 3 + x Solving -7 + 7x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 7x + -1x = 3 + x + -1x Combine like terms: 7x + -1x = 6x -7 + 6x = 3 + x + -1x Combine like terms: x + -1x = 0 -7 + 6x = 3 + 0 -7 + 6x = 3 Add '7' to each side of the equation. -7 + 7 + 6x = 3 + 7 Combine like terms: -7 + 7 = 0 0 + 6x = 3 + 7 6x = 3 + 7 Combine like terms: 3 + 7 = 10 6x = 10 Divide each side by '6'. x = 1.666666667 Simplifying x = 1.666666667
| -5=-5x | | 2x^4+x^3-3x^2+x+2=0 | | 9-3(x-1)=2x | | 4(2x-1)=x+3 | | X=2.5 | | -x^2-1+2m=0 | | 21-2x=5x-10.5 | | 4x+3+5x=6 | | 115-2x=16x+23 | | -25=5(1-2x) | | x-1=3x+3 | | x-15=-20 | | x^3+8x^2+9x=0 | | 6y=-6x-6 | | 88-3x=10x+32 | | x*11+4=y | | 6x+7+91=6x | | x^2+3x-13=8x+1 | | 29=21-4x | | 2x+38=1-x-58 | | x*8+72=y | | x^2-9x+22=4 | | 2(x+7)-(x+1)=0 | | 3-2(2+x)=x+5 | | 10x-143=5x-13 | | (3x+4)=(5x-7) | | 12-8x=57-43x | | 7X*7X=5X | | -4x*3+8x=0 | | (2x-3)-(-x+6)= | | -31-4x=5-10 | | 2x^6+3= |